Hidden Curriculum di Pesantren Ash-haburratib Kota Depok dalam Pengembangan Soft Skill Santri - Malena Nurhayati; Hindun Hindun (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Research on the hidden curriculum at the Ash-haburratib Islamic Boarding School, Depok City and its impact on the development of students' soft skills. The research was carried out using a qualitative approach through in-depth interviews, observation and analysis of related documents. Ash-haburratib Islamic boarding school was found to have a hidden curriculum that not only includes religious aspects, but also involves social aspects, leadership and interpersonal skills. The research results show that this Islamic boarding school indirectly encourages the development of students' soft skills through daily interactions, extracurricular activities, and participation in independent activities. This hidden curriculum makes a positive contribution to improving students' communication, leadership and collaboration skills. Apart from that, Islamic boarding schools also provide space for students to develop moral and ethical values ​​that support the formation of strong character. This research provides in-depth insight into how the hidden curriculum in Islamic boarding schools can be an effective means of forming students' soft skills. The implications of this research can help Islamic boarding school managers and educators to better understand the role of the hidden curriculum in soft skills development, as well as provide a basis for improving and developing a more structured curriculum.